2010
DOI: 10.1016/j.coph.2009.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid–opioid interactions during neuropathic pain and analgesia

Abstract: Opiates and exogenous cannabinoids, both potent analgesics used for the treatment of patients with neuropathic pain, bind to and activate class A G-protein coupled receptors (GPCRs). Several lines of evidence have recently suggested that opioid and cannabinoid receptors can functionally interact in the central nervous system (CNS). These interactions may be direct, such as through receptor heteromerization, or indirect, such as through signaling cross-talk that includes agonist-mediated release and/or synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
109
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(113 citation statements)
references
References 67 publications
1
109
1
2
Order By: Relevance
“…Analgesics targeting the endogenous opioid system are the most commonly prescribed (Trescot et al, 2008) and the opioid system is well recognised to modulate acute, inflammatory and neuropathic pain (Bushlin et al, 2010;Przewłocki and Przewłocka, 2001). This system is composed of the μ (mu)-, δ (delta)-, and κ(kappa)-opioid receptors.…”
Section: Opioidsmentioning
confidence: 99%
“…Analgesics targeting the endogenous opioid system are the most commonly prescribed (Trescot et al, 2008) and the opioid system is well recognised to modulate acute, inflammatory and neuropathic pain (Bushlin et al, 2010;Przewłocki and Przewłocka, 2001). This system is composed of the μ (mu)-, δ (delta)-, and κ(kappa)-opioid receptors.…”
Section: Opioidsmentioning
confidence: 99%
“…Thus, they propose combining opioid and cannabinoid agonists or targeting receptor heteromers directly. These new ideas are in need of exploration, but show promising potential in diminishing chronic pain [96], representing a starting point in the new avenue unfolding in the story of pain treatment.…”
Section: Schizophrenia Pain and Plantsmentioning
confidence: 99%
“…Moreover, an interesting connection between cannabinoids and opioids has been recently highlighted, that might open new opportunities in the treatment of neuropathic pain and in the development of new analgesics. There has been emphasized on the synergism between the cannabinoid-opioid receptor systems, showing that low doses of cannabinoid agonists combined with opioid agonist have a promising outcome [96]. Although, tolerance and cross-tolerance must not be ignored, occurrence of addiction phenomenon is another impediment adding to their limiting usage on the long run [96].…”
Section: Schizophrenia Pain and Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence has been accumulating from molecular and cell-signaling studies that suggest that the opioids and cannabinoid systems can interact synergistically to enhance analgesic effects. 49 Animal studies have shown that topical cannabinoid enhances the action of topical morphine, 50 an effect that is preserved in a morphine-tolerant state. 51 Moreover, cannabinoids are increasingly being recognized in animal models for their potential sparing effects with opioids 52 of neuropathic pain and arthritic pain.…”
Section: Analgesic Potential and Synergism With Opioidsmentioning
confidence: 99%